2008
DOI: 10.1080/17461390802116658
|View full text |Cite
|
Sign up to set email alerts
|

Post‐exercise coincidence anticipation in expert and novice Gaelic games players: the effects of exercise intensity

Abstract: Within the current scientific literature, there is a distinct lack of empirical data examining the effects of exercise intensity on\ud coincidence anticipation and, to date, no study has examined this in Gaelic games. Furthermore, many previous studies failed to consider fully sport specificity. The aims of this study were to examine the effect of moderate- and high-intensity\ud exercise on coincidence anticipation and to determine whether post-exercise changes in coincidence anticipation were the same in novi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 44 publications
9
43
0
1
Order By: Relevance
“…A considerable amount of literature has been published on age (Benguigui & Ripoll, 1998;Vanttinen, Blomqvist, Luhtanen, & Hakkinen, 2010), gender (Millslagle, 2004;Sanders & Sinclair, 2011), skill levels (Lyons, Al-Nakeeb, & Nevill, 2008;Tenenbaum, Sar-El, & Bar-Eli, 2000), and sports type (Ak & Koçak, 2010;Akpinar, Devrilmez, & Kirazci, 2012), however literatures is still lacking in relation of VAT to the sporting environment. Researchers found higher accuracy and consistency in anticipation ability depending on the sports involved.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable amount of literature has been published on age (Benguigui & Ripoll, 1998;Vanttinen, Blomqvist, Luhtanen, & Hakkinen, 2010), gender (Millslagle, 2004;Sanders & Sinclair, 2011), skill levels (Lyons, Al-Nakeeb, & Nevill, 2008;Tenenbaum, Sar-El, & Bar-Eli, 2000), and sports type (Ak & Koçak, 2010;Akpinar, Devrilmez, & Kirazci, 2012), however literatures is still lacking in relation of VAT to the sporting environment. Researchers found higher accuracy and consistency in anticipation ability depending on the sports involved.…”
Section: Introductionmentioning
confidence: 99%
“…CE, which is error resulting from a directional trend, [ 35 ] is the temporal interval (in milliseconds) between the arrival of the visual stimulus and the end of the participant's motor response. [ 36 ] The calculation was done by the simple arithmetic average of the error values, considering the algebraic sign (negative or positive) in a series of attempts (block of trials). It represents the direction of error if it is late or early.…”
Section: Methodsmentioning
confidence: 99%
“…[ 35 ] It was calculated by taking the absolute value of each raw score, disregarding whether the response was early or late. [ 36 ] VE is the error resulting from within-subject variability. [ 35 ] It represents the consistency in a group of responses and is independent of the proximity of each trial to the designated target.…”
Section: Methodsmentioning
confidence: 99%
“…Research has revealed the height of the average player ranges between 177-182 cm and weight ranging from 78.5-89.5 kg (10,30,31,32,33,34,35,36). The rationale for measuring an athlete's body composition is to regulate body fat and encourage weight management to maximise performance (13).…”
Section: Anthropometrymentioning
confidence: 99%